Genome‐wide investigation of intragenic DNA methylation identifies ZMIZ1 gene as a prognostic marker in glioblastoma and multiple cancer types. Issue 12 (9th August 2019) - Mathios, Dimitrios; Hwang, Taeyoung; Xia, Yuanxuan; Phallen, Jillian; Rui, Yuan; See, Alfred P.; Maxwell, Russell; Belcaid, Zineb; Casaos, Joshua; Burger, Peter C.; McDonald, Kerrie L.; Gallia, Gary L.; et al.
Abstract : DNA methylation has long been recognized as a tumor‐promoting factor when aberrantly regulated in the promoter region of genes. However, the effect of intragenic DNA methylation remains poorly understood on the clinical aspects of cancer. Here, we first evaluated the significance of intragenic DNA methylation for survival outcomes of cancer patients in a genome‐wide manner. Glioblastoma patients with hypermethylated intragenic regions exhibited better survival than hypomethylated patients. Enrichment analyses of intragenic DNA methylation profiles with epigenetic signatures prioritized the intragenic DNA methylation of ZMIZ1 as a possible glioblastoma prognostic marker that is independent of MGMT methylation in IDH1 wild‐type patients. This intragenic region harbored molecular signatures of alternative transcription across many cell types. Furthermore, we found that the intragenic region of ZMIZ1 can serve as a molecular marker in multiple cancers including astrocytomas, bladder cancer and renal cell carcinoma according to DNA methylation status. Finally, in vitro and in vivo experiments uncovered the role of ZMIZ1 as a driver of tumor cell migration. Altogether, our results identify ZMIZ1 as a prognostic marker in cancer and highlight the clinical significance of intragenic methylation in cancer. Abstract : What's new? Aberrant methylation of the promoter region of various genes has long been recognized as a tumor‐promoting factor. But what about intragenic DNA? In this genome‐wide study, the authors found that intragenic DNA methylation of the ZMIZ1 gene can predict outcomes in multiple solid cancers, especially glioblastoma, astrocytoma, bladder cancer, and renal‐cell carcinoma. Evidence from independent clinical cohorts, as well as from preclinical experiments, showed that intragenic ZMIZ1 methylation affects overall survival in cancer patients, and tumor‐cell migration in vivo . These results indicate that ZMIZ1 may provide a useful prognostic biomarker for various cancers.